Faucet: Deploying SDN in the Enterprise. - BAILEY, JOSH; STUART, STEPHEN (Communications of the ACM, 2017)
The article discusses the use of open source software-defined networking (SDN) in enterprise networks. Topics include the use of the Faucet network by the organization Open Networking Foundation, the testing and deployment of networking software, and the role of a control-plane network (CPN) in network security.